WEB Application Security Testing: A Practical Example of Laboratory Setup - Piotr KONTOWICZ (Communications of International Proceedings, 2024)
This document outlines a comprehensive framework for web application security training, using a structured, isolated environment to cover both basic and advanced vulnerability classes. Leveraging VirtualBox, it demonstrates a virtual lab setup with a tester machine and a vulnerable web application, focusing on hands-on exercises like Capture The Flag (CTF) challenges to help participants master prevalent security issues. Aligned with real-world scenarios through the inclusion of OWASP Top Ten vulnerabilities, this setup ensures practical, applicable learning. Future enhancements will introduce remote server-based environments, enabling scalable, individualized instances to prevent interference and optimize learning. Designed for academic and professional use, this framework provides a robust foundation for developing security expertise in a realistic, controlled setting.
Keywords: Web Application Security; Security Testing Environment; Penetration Testing.